Association between Maternal Exposure to Chemicals during Pregnancy and the Risk of Foetal Death: The Japan Environment and Children’s Study - Tadao Ooka (MDPI AG, 2021)
Scarce knowledge is available on the relationship between maternal chemical exposure during pregnancy and foetal deaths. We studied the association of spontaneous abortions and stillbirths with occupational or daily maternal exposure to chemicals commonly used by pregnant women. Data from the Japan Environment and Children’s Study (JECS), a nationwide prospective birth cohort study, were used. The participants of the study were asked about the frequency of their use of gasoline, pesticides, hair dye, and chlorine bleach during the first and the second to third trimesters of pregnancy. We investigated the relationship between the frequency of the use of chemicals and foetal death. Of the 104,065 foetuses, 923 (0.91%) were spontaneous abortions and 379 (0.37%) were stillbirths. Any type of exposure during the first trimester was not significantly associated with spontaneous abortions. Nevertheless, a more than weekly occupational use of hair dye from the first to the second/third trimester was significantly associated with stillbirth. The results of this study suggest that the frequent use of hair dye during pregnancy can have severe adverse effects on the foetus. These findings can help pregnant women, especially hairdressers, refrain from the continuous use of hair dyes.